2003
DOI: 10.1136/bjsm.37.6.550
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of heart rate variability measures at rest and during light exercise in children

Abstract: Objective: To examine the absolute and relative changes in skeletal muscle (SM) size using whole body magnetic resonance imaging (MRI) in response to heavy resistance training (RT). Method: Three young men trained three days a week for 16 weeks. Results: MRI measured total SM mass and fat free mass (FFM) had increased by 4.2 kg and 2.6 kg respectively after resistance training. Conclusions: RT induces larger increases in SM mass than in FFM. RT induced muscle hypertrophy does not occur uniformly throughout eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
36
2
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 21 publications
8
36
2
11
Order By: Relevance
“…Interestingly, when assessed separately, a significant association between 24-h physical activity and diminished sympathovagal imbalance in children was observed [5,48]. However, while larger BMI was not associated with HRV, larger waist circumference was related to reduced VLF, which is partly consistent with past pediatric findings of greater obesity linked to reduced HRV [16,22,33].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, when assessed separately, a significant association between 24-h physical activity and diminished sympathovagal imbalance in children was observed [5,48]. However, while larger BMI was not associated with HRV, larger waist circumference was related to reduced VLF, which is partly consistent with past pediatric findings of greater obesity linked to reduced HRV [16,22,33].…”
Section: Resultssupporting
confidence: 83%
“…When all covariates were included in the models simultaneously, heart rate (β avg = −0. [19,48]. No comparisons could be made for SDANN and SDNNi, as they are infrequently reported in studies.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to previous reliability studies, the current study reported greater reproducibility (e.g., lower CV and/or lower LOA) for HRV during rest and light exercise over the 8-week period (11,18,37). Previous recommendations of greater control of external influences such as time of recording, overnight fast and restriction of tobacco or caffeine (11,18,37) were followed in the current study and may have contributed to the greater HRV reliability compared to these prior studies.…”
Section: Discussioncontrasting
confidence: 40%
“…Winsley et al (2003) [16] pointed out the importance of tight control of external influences. In the present research that was not achieved at all times.…”
Section: Discussionmentioning
confidence: 99%